2021
DOI: 10.21203/rs.3.rs-1001073/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synbiotic Supplementation And Oxalate Homeostasis In Rats: Focus On Microbiota Oxalate-Degrading Activity

Abstract: Background The present study aimed (i) to evaluate whether ceftriaxone treatment could affect not only intestinal oxalate-degrading bacteria number but their total activity to degrade oxalate and influence oxalate homeostasis in rats, (ii) to test the effect of commercially available probiotics and a synbiotic on total fecal oxalate-degrading activity, (iii) and to estimate the ability of synbiotic to restore fecal oxalate-degrading activity and ceftriaxone-induced disruption of oxalate homeostasis in rats. Me… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Hence, there is a recent interest in the modulation of the intestinal microbiota through the oral administration of probiotics to influence the initiation and development of kidney stones. In a study with rats treated with ceftriaxone, a synbiotic composed by Lactobacillus acidophilus , Lactobacillus rhamnosus , Lactobacillus plantarum , Lactobacillus casei , Bifidobacterium bifidum , Bifidobacterium longum , Saccharomyces boulardii , oligofructose and inulin restored oxalate-degrading activity and decreased urinary oxalate excretion independently of the number of oxalate-degrading bacteria [27 ▪ ]. In a murine model of hyperoxaluria induced by ethylene glycol, it was also observed that intestinal inflammation and increased intestinal permeability were produced.…”
Section: Probiotics and Kidney Stone Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Hence, there is a recent interest in the modulation of the intestinal microbiota through the oral administration of probiotics to influence the initiation and development of kidney stones. In a study with rats treated with ceftriaxone, a synbiotic composed by Lactobacillus acidophilus , Lactobacillus rhamnosus , Lactobacillus plantarum , Lactobacillus casei , Bifidobacterium bifidum , Bifidobacterium longum , Saccharomyces boulardii , oligofructose and inulin restored oxalate-degrading activity and decreased urinary oxalate excretion independently of the number of oxalate-degrading bacteria [27 ▪ ]. In a murine model of hyperoxaluria induced by ethylene glycol, it was also observed that intestinal inflammation and increased intestinal permeability were produced.…”
Section: Probiotics and Kidney Stone Diseasementioning
confidence: 99%
“…Gut microbiota preferentially uses the oxalate degradation pathway type II, which consists of a two-step reaction involving enzymes such as formyl-CoA transferase and oxalyl-CoA decarboxylase, with coenzyme A as a cofactor [26 ▪▪ ]. Another study in rats has shown that oxalate-degrading activity, but not the number of oxalate-degrading bacteria, should be examined as a diagnostic predictive tool, in prevention and personalized KSD treatment [27 ▪ ]. Another example of the relationship between gut microbiota and the KSD pathogenesis is that in a murine model of induced urolithiasis, administration of a solution with KSD patient feces increased crystal formation and accelerated stone formation [28 ▪ ].…”
Section: Gut Microbiome and Kidney Stone Diseasementioning
confidence: 99%
“…Previous research by Balthazar et al has shown that among prebiotics, inulin may cause increase survival and activity of lactic acid bacteria during shelf life [26]. Stepanova et al showed that impact of prebiotics on increased degradation of oxalate is due to the increased growth of bacteria resulted from the presence of short chain free fatty acids [27]. Another study in 2018 by Darilmaz et al Showed that prebiotics could increase the degradation of oxalate by lactobacilli in vitro.…”
Section: Inulinmentioning
confidence: 99%